Differences in obstetric practices and outcomes of postpartum hemorrhage across Nigerian health facilities. (28th June 2022) - Wakili, Aminu Ado; Aswat, Ashraf; Timms, Rebecca; Beeson, Leanne; Mammoliti, Kristie‐Marie; Devall, Adam; Musa, Baba Maiyaki; Amole, Taiwo; Dankishiya, Faisal; Coomarasamy, Arri; Gallos, Ioannis D.; Galadanci, Hadiza S.
Abstract: Objective: To explore differences in obstetric practices and clinical outcomes of postpartum hemorrhage (PPH) in Nigerian facilities. Methods: A descriptive cross‐sectional study of public health facilities providing maternal healthcare services in Nigeria. Surveys were conducted across 38 purposively sampled facilities (January 2020–March 2021) to collect information on obstetric practices related to the management of the third stage of labor, treatment of postpartum hemorrhage, and clinical outcomes related to postpartum hemorrhage in the preceding 12 months. Results: The median number of annual births per facility was 2230 (IQR, 1952–3283). The cesarean section rate was 21.6% (range 2.1%–52.6%). There was large variability in PPH rate (median 3%, range 0.4%–16.8%) and blood transfusions for PPH (median 2.8%, range 0.4%–48.6%) after vaginal birth. There was less variability for laparotomies (median 0.25%, range 0%–2.8%) and maternal deaths (median 0.11%, range 0%–0.64%) due to PPH after vaginal birth. The number of maternal deaths from all causes varied (median 0.27%, range 0%–3.5%). The rates of PPH and adverse maternal outcomes did not vary substantially between state or federal facilities, region, type of facility, and the number of clinical staff. Conclusion: Across the Nigerian facilities surveyed there was large variation in PPH rates and adverse maternal outcomes due to PPH. This variability remains largely unexplained and requires further insights and detailed data to gain a deeper understanding of the root causes and challenges to implement customized solutions to improve maternal outcomes. Synopsis: There is large, unexplained variability in obstetric practices, rates of postpartum hemorrhage, laparotomies, and deaths due to postpartum hemorrhage across Nigerian facilities.